Treatment of Couples Experiencing Pregnancy Loss: Reauthoring Loss from a Narrative Perspective. Issue 2 (3rd April 2021) - Romney, Justin; Fife, Stephen T.; Sanders, Daniel; Behrens, Sarah
ABSTRACT: Pregnancy loss is a traumatic event that affects many families. 1 in 5 pregnancies end in miscarriage, and 1–2 out of every 100 births are stillbirths. Mothers report depression, shame, and guilt following a pregnancy loss. They also report a lack of social and emotional support, as Western culture tends to discourage mothers from grieving. Additionally, the impact on partners often goes unnoticed, as pregnancy loss is primarily framed as a birth parent's issue. As couples struggle to deal with the emotions of pregnancy loss, many approach the process of grieving in ways that inhibit healing, which can negatively impact their relationship. Given the potential difficulties, many couples seek therapy to help them with the challenges that may follow pregnancy loss. However, there is a lack of literature that discusses how to systemically treat pregnancy loss. This article aims to address that gap by presenting a narrative approach to treating pregnancy loss. Narrative therapy is a natural fit when treating grieving couples as it allows them to coauthor their story of loss and coauthor a story of healing. Narrative therapy provides a space for couples to share their story, externalize problems related to the loss, find unique outcomes to support an alternative story, and solidify a new narrative related to their pregnancy loss.